A study on Donald Trump Twitter remark: a case study on the attack of Capitol Hill / Mohd Razman Achmadi Muhammad and Noor Nirwandy - Muhammad, Mohd Razman Achmadi; Nirwandy, Noor (Centre For Media And Information Warfare Studies, 2021)
Twitter has grown in popularity as one of the most popular means of political communication. Trump was known as one of the platform's most prolific politician users [1]. Prior to the 2020 election, Trump tweeted a series of false allegations regarding the election and continues to do so even after the election. After two months of constant attack and accusations, on 6th January 2021 Capitol Hill was attacked by his supporters. Hours before the attack, Trump ended up his speech at the 'Save America Rally" by calling for his supporters to march towards the Congress and eventually, a riot broke out at Capitol Hill [2]. Therefore, this research will explore and identify how Trump uses Twitter to sets his agenda and propagate his allegation of electoral fraud prior to the insurrection. By using qualitative research method, this study succeeded in identifying Trump's agenda-setting and was well received by his supporters which resulted in the storming of Capitol Hill. This research concluded that agenda-setting through social media is applicable when a politician created an issue to be debated by the mainstream media and the public. The study also found that social media can evoke emotional reactions that caused real-life threats and property destruction.